Peningkatan prestasi belajar siswa dalam pembelajaran bahasa arab menggunakan media kartu bergambar pada siswa - Syofiarti, Syofiarti (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The background of this study was the students' difficulties in memorizing the materials of school equipment. Problem solving is needed by using of effective  and easily obtainable learning media such as pictured card (flash card) media,  based on group  in the classroom.  The purpose of this study was to enhance vocabulary mastery of Arabic (mufradat) students on the material of school equipment of students in grade VII.I with core competence (KI) understand and apply the knowledge (factual, conceptual, and procedural) based on their curiosity about science, technology , cultural arts related phenomena and visible eye events. The results showed  an increase in students' mastery of Arabic vocabulary using word picture card media. The score average of cycle I is 71,22 and on cycle II increases to 78,11. These competencies can be seen from the first indicator, students happy and active in learning activities. Second indicator ,  increasing the ability of students in material of school equipment. Students are able to create their own concepts of learning materials from the results of group learning activities other than teacher presentation. Teacher only as a mentor. this instructional model is recommended to the mtsn teacher as an alternative to improve students' ability on the material of school equipment. From the research, it can be concluded that the using of flashcard can improve  the student  learning outcomes  in grade VII.I MTsN Bonjol on the material of school equipment. This learning application based on group can improve student’s skills in the school equipment.